Obesity causes PGC‐1α deficiency in the pancreas leading to marked IL‐6 upregulation via NF‐κB in acute pancreatitis. Issue 1 (11th December 2018) - Pérez, Salvador; Rius‐Pérez, Sergio; Finamor, Isabela; Martí‐Andrés, Pablo; Prieto, Ignacio; García, Raquel; Monsalve, María; Sastre, Juan
Abstract: Obesity is associated with local and systemic complications in acute pancreatitis. PPARγ coactivator 1α (PGC‐1α) is a transcriptional coactivator and master regulator of mitochondrial biogenesis that exhibits dysregulation in obese subjects. Our aims were: (1) to study PGC‐1α levels in pancreas from lean or obese rats and mice with acute pancreatitis; and (2) to determine the role of PGC‐1α in the inflammatory response during acute pancreatitis elucidating the signaling pathways regulated by PGC‐1α. Lean and obese Zucker rats and lean and obese C57BL6 mice were used first; subsequently, wild‐type and PGC‐1α knockout (KO) mice with cerulein‐induced pancreatitis were used to assess the inflammatory response and expression of target genes. Ppargc1a mRNA and protein levels were markedly downregulated in pancreas of obese rats and mice versus lean animals. PGC‐1α protein levels increased in pancreas of lean mice with acute pancreatitis, but not in obese mice with pancreatitis. Interleukin‐6 (Il6) mRNA levels were dramatically upregulated in pancreas of PGC‐1α KO mice after cerulein‐induced pancreatitis in comparison with wild‐type mice with pancreatitis. Edema and the inflammatory infiltrate were more intense in pancreas from PGC‐1α KO mice than in wild‐type mice. The lack of PGC‐1α markedly enhanced nuclear translocation of phospho‐p65 and recruitment of p65 to Il6 promoter. PGC‐1α bound phospho‐p65 in pancreas during pancreatitis in wild‐type mice. Glutathione depletion in cerulein‐induced pancreatitis was more severe in KO mice than in wild‐type mice. PGC‐1α KO mice with pancreatitis, but not wild‐type mice, exhibited increased myeloperoxidase activity in the lungs, together with alveolar wall thickening and collapse, which were abrogated by blockade of the IL‐6 receptor glycoprotein 130 with LMT‐28. In conclusion, obese rodents exhibit PGC‐1α deficiency in the pancreas. PGC‐1α acts as selective repressor of nuclear factor‐κB (NF‐κB) towards IL‐6 in pancreas. PGC‐1α deficiency markedly enhanced NF‐κB‐mediated upregulation of Il6 in pancreas in pancreatitis, leading to a severe inflammatory response. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.